Postgraduate students’ perceptions towards using subtitled movies in improving English language / Raihannah Khairyn Kamaruddin, Aini Faridah Azizul Hassan and Norwati Roslim - Kamaruddin, Raihannah Khairyn; Azizul, Aini Faridah; Roslim, Norwati (Universiti Teknologi MARA, Kedah, 2024)
Educators are always searching for interesting and innovative ways to help language learners—especially adults—to learn language effectively, as language acquisition is often challenging for them. Nowadays, one of the most effective ways to learn languages is by using movies with subtitles. This is because subtitled movies provide entertainment and contribute to many language inputs, as the combination of audiovisual elements and text in them can create an authentic learning experience. Therefore, this study explores the effect of subtitled movies on English language acquisition among postgraduate students. The research employed a qualitative method where semi-structured interviews were conducted by interviewing 12 postgraduate students from a local university in Malaysia. The findings revealed that subtitled movies are effective in language learning, especially in improving vocabulary, understanding accent and slang, and enhancing language skills such as pronunciation, writing and reading. Hence, this study demonstrates the potential of subtitled movies as valuable learning material in language learning, suggesting their integration into the education curriculum and contributing to the growing research on the use of subtitled movies in language learning for postgraduate students. This study may also provide insightful understanding for educators and policymakers regarding creative teaching strategies in the field of language education.